2017
DOI: 10.1175/mwr-d-16-0263.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Tropospheric Precursors to the Formation of Subtropical Cyclones that Undergo Tropical Transition in the North Atlantic Basin

Abstract: The opportunity to examine the structure and evolution of the various upper-tropospheric precursors to the formation of North Atlantic (NATL) subtropical cyclones (STCs) that undergo tropical transition (TT) motivates this study. Intraseasonal variability associated with the location and frequency of NATL STCs forming in the presence of similar upper-tropospheric features, as well as similarities and differences in the various upper-tropospheric precursors to the formation of NATL STCs that undergo TT, are exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…In case of the RCM‐modelled STCs, the distribution is similar to the observed values, as there is a distinct prevalence of STCs over winter months, although the observed March peak is not reproduced in the simulations. The higher prevalence in winter months gives support to the fact that the simulated STCs mainly develop from extratropical precursors, a relationship shown in observational studies (González‐Alemán et al, , Evans and Guishard, , Guishard et al, , Bentley et al, , ). Extratropical precursors such as upper‐level troughs and cut‐off lows are more likely to reach the subtropical domain in winter as the southern edge of the upper‐level midlatitude circulation is located at its southernmost position.…”
Section: Rcms Nested In Gcms In the Historical Period (1951–2000)mentioning
confidence: 87%
See 1 more Smart Citation
“…In case of the RCM‐modelled STCs, the distribution is similar to the observed values, as there is a distinct prevalence of STCs over winter months, although the observed March peak is not reproduced in the simulations. The higher prevalence in winter months gives support to the fact that the simulated STCs mainly develop from extratropical precursors, a relationship shown in observational studies (González‐Alemán et al, , Evans and Guishard, , Guishard et al, , Bentley et al, , ). Extratropical precursors such as upper‐level troughs and cut‐off lows are more likely to reach the subtropical domain in winter as the southern edge of the upper‐level midlatitude circulation is located at its southernmost position.…”
Section: Rcms Nested In Gcms In the Historical Period (1951–2000)mentioning
confidence: 87%
“…As STCs have strong connections to the atmospheric dynamics in the extratropics and subtropics (they form from extratropical precursors; Evans and Guishard, 2009; * Correspondence to: J. J. González-Alemán, Environmental Sciences Institute, University of Castilla-La Mancha, Avenida Carlos III, s/n, Toledo 45071, Spain. E-mail: juanjesus.gonzalez@uclm.es González-Alemán et al, 2015;Bentley et al, 2017) and to the ocean in their lower boundary (through sea surface temperatures (SSTs) or warm-air advections) González-Alemán et al, 2015), it is worth researching if anthropogenic climate change (ACC) could cause changes in their formation. Alterations in the atmospheric patterns over the extratropics and subtropics projected for future climate conditions (Thorne et al, 2011;Vavrus, 2012, 2015) as well as alterations in SSTs distribution (Collins et al, 2013) may lead to changes in their frequency of occurrence, location and/or intensity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a cut-off low or stratospheric PV streamer in the upper troposphere associated with anticyclonic Rossby wave breaking (Martius et al, 2007;Waugh & Polvani, 2000;Wernli & Sprenger, 2007) can initiate organized deep convection (e.g., Waugh & Funatsu, 2003) and a subtropical cyclone (e.g., Galarneau et al, 2015) by destabilizing the troposphere (Juckes & Smith, 2000) or through QG forcing for ascent (Hoskins et al, 1985;Trenberth, 1978). Some of these subtropical cyclones occasionally develop into TCs as they travel across a warm SST region (Bentley et al, 2017).…”
Section: Evolution Of the Upper Tropospheric Disturbancementioning
confidence: 99%
“…Alternatively, the colder and drier air transported into the upper troposphere serves to destabilize the tropospheric column by enhancing convective available potential energy (CAPE), thus to foster convectively favorable environments (Juckes & Smith, 2000). The associated anticyclonic wave breaking (and PV streamer) over the tropical eastern Pacific and North Atlantic has been attributed to the formation of subtropical cyclones, which can subsequently undergo tropical transition (Bentley et al, 2017;Bentley & Metz, 2016;Davis & Bosart, 2003Galarneau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The midlatitude wave teleconnection is stronger in regime 4 compared to regime 5, while the anomalous ridge is seen to retrograde southwestwards leading to significant positive pressure anomalies in the upper‐troposphere over the southwest United States and negative anomalies over the southeast for regime 6. This sequence of upper‐tropospheric configurations is reminescent of the behaviour of potential vorticity (PV) ‘streamers’ during anticyclonic wave breaking (Thorncroft et al ., ; Davis, ) and which have been related to subtropical cyclone formation in the North Atlantic in previous works (Bentley, ). PV streamers inject regions of relatively high upper‐tropospheric PV into the subtropical lower troposphere, which become advected westward by the mean easterlies and CLLJ during the sequence of regimes 4–6.…”
Section: Propagating Convective Cellsmentioning
confidence: 99%